Scavenging Activity on Reactive Oxygen Species with Biological Relevance by Varronia curassavica - Veloso, Gabriela Brasil Romão [UNESP]; Assis, Renata Pires [UNESP]; Pereira, Juhan Augusto Scardelato [UNESP]; Carvalho, Flávio Alexandre [UNESP]; Soares, Christiane Pienna [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Isaac, Vera Lucia Borges [UNESP]; Ricelli, Paulo; Zocolo, Guilherme; Corrêa, Marcos Antônio [UNESP]; dos Santos, André Gonzaga [UNESP] (Instituto de Quimica - Univ. Federal do Mato Grosso do Sul, 2023)
Varronia curassavica Jacq. is a medicinal plant found in Brazil used as anti-inflammatory. Here, we investigated the in vitro antioxidant activity of 70 % ethanol extract of V. curassavica leaves on synthetic radicals (ABTS-/DPPH·) and reactive oxygen species (O2·-, ROO·, HOCl/OCl-, H2O2), besides its in vitro cytotoxicity. The extract was characterized by UPLC-ESI-QToF-MSE and the annotated compounds were one hydroxybenzoic acid, five phenylpropanoids, and three glycosylated quercetin derivatives, being the main compound rosmarinic acid or its isomer. The antioxidant activity was very promising in all tests, highlighting on the capture of O2·-, which EC50 value was three times lower than Trolox. This activity may be due to the presence of the major compounds, all phenolic compounds. The extract also presented low cytotoxicity. Thus, the extract from V. curassavica leaves has great potential as an antioxidant.
Keywords: Antioxidant; Cytotoxicity; Oxidative stress; Reactive oxygen species (ROS)